FACTORS INFLUENCING BRAND LOYALTY IN FAST FOOD RESTAURANTS IN INDONESIA - Santoso, Kenneth; Luki Adiati Pratomo (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2025)
This study aims to assess the positive impact of brand identification, self-image expression, perception of the natural environment, and layout on brand passion, brand love, brand pride, and brand loyalty, as well as the positive effect of brand passion, brand love, and brand pride on brand loyalty. The data analysis technique employed in this study is structural equation modeling (SEM), which serves as a robust multivariate tool for testing research hypotheses using AMOS version 23. The results reveal that identity-based attachment and place dependence attachment positively influence emotion-based attachment and brand loyalty, with both dimensions also showing a direct positive effect on brand loyalty. This study offers valuable insights and suggestions for future research by recommending the inclusion of new independent variables such as food quality and customer satisfaction quality. Furthermore, incorporating additional fast-food brands in Indonesia is advised to broaden the study scope.